"The Million Dead, Too, Summ'd Up" : Walt Whitman's Civil War Writings - Whitman, Walt, 1819-1892 (Book collections on Project MUSE., 2021)
"This book is the first to offer a comprehensive selection of Walt Whitman's Civil War poetry and prose with a full commentary on each work. One of the most distinguished critics in Whitman Studies, Ed Folsom, and one of the nation's most prominent writers and literary figures, Christopher Merrill, carry on a dialog with Whitman (and with each other), selection by selection, as they invite readers to enter into the conversation about how Whitman's writing about the Civil War develops, shifts, and manifests itself in different genres throughout the four years of the war. Folsom and Merrill go beyond Whitman's well-known war poems in his Drum-Taps and examine with equal care his Civil War prose writing in Memoranda During the War and in his personal letters. The book offers forty selections of Whitman's war writings, each followed by Folsom's detailed critical examination of the work and then by Merrill's writer's afterword, suggesting broader contexts for thinking about the selection. The Civil War initially shattered Whitman's confidence in the future of the nation he invested so much faith in, but he gradually reconciled himself to the idea that the war ultimately would strengthen the reconstructed United States and would serve as the compost out of which a great democratic future would be built. Folsom and Merrill offer a commentary that takes to heart Whitman's faith in an emerging democratic readership. The real democratic reader, Whitman said, "must himself or herself construct indeed the poem, argument, history, metaphysical essay-the text furnishing the hints, the clue, the start or frame-work," because what is needed for democracy to flourish is "a nation of supple and athletic minds." This book-like our previous one on Whitman's "Song of Myself"-sets out to model this active kind of reading and to encourage both seasoned and new readers of Whitman's war writings to enter into the challenging and exhilarating mode of talking back to Whitman, of engaging him, arguing with him, learning from him, and articulating ways that his responses to America's defining traumatic event continue to speak in surprising new ways to present-day America and to the world beyond America"--